Sosialisasi Penanggulangan Pencegahan Covid-19 di Kelurahan Kamalaputi Kab. Sumba Timur Tahun 2021 - Rambu H Indah; Rambu S.M.Maramba (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The increase in COVID-19 cases in general cannot be separated from the level of community compliance and awareness to obey the health procedures. In 2021 the number of COVID-19 in NTT will reach 2,336 people. The data seen on the Covid-19 website itself shows a lack of public awareness of the dangers of the Corona Virus, and there are still many people who are indifferent, which are often seen in crowds, not wearing masks and obeying health procedures. Seeing this situation, the implementation of the PKM Covid-19 Handling Socialization in the Kamalaputi sub-district aims to provide counseling on the impact of covid-19 and non-compliance with the law. The methods carried out are in the form of counseling and providing information about the importance of implementing health protocols and clean living behavior, diligently washing hands with soap, using masks when doing activities outside the home and maintaining a safe distance when in public places. The Kamalaputih sub-district community also distributes free masks to road users. As for the final output in the implementation of this PKM, the community becomes obedient to the health procedures and is aware of the importance of taking care of themselves by using masks and obeying health procedures.